Ultrafast processes triggered by one- and two-photon excitation of a photochromic and luminescent hydrazone - Iagatti, Alessandro; Shao, Baihao; Credi, Alberto; Ventura, Barbara; Aprahamian, Ivan; Di Donato, Mariangela (Beilstein Journal of Organic Chemistry, 2019)
In this work we apply a combination of steady state and time resolved luminescence and absorption spectroscopies to investigate the excited-state dynamics of a recently developed molecular photoswitch, belonging to the hydrazone family. The outstanding properties of this molecule, involving fluorescence toggling, bistability, high isomerization quantum yield and non-negligible two-photon absorption cross section, make it very promising for numerous applications. Here we show that the light induced Z/E isomerization occurs on a fast <1 ps timescale in both toluene and acetonitrile, while the excited state lifetime of the Z-form depends on solvent polarity, suggesting a partial charge transfer nature of its low lying excited state. Time-resolved luminescence measurements evidence the presence of a main emission component in the 500–520 nm spectral range, attributed to the Z-isomer, and a very short living blue-shifted emission, attributed to the E-isomer. Finally, transient absorption measurements performed upon far-red excitation are employed as an alternative method to determine the two-photon absorption cross-section of the molecule.
Keywords: hydrazone; molecular switch; pump-probe spectroscopy; time-resolved fluorescence

Molecular Switches - Feringa, B. L.; Browne, W. R. (Wiley-VCH, 2011)

(untitled) - Klajn, R.; Stoddart, J. F.; Grzybowski, B. A. (Chem. Soc. Rev., 2010)

(untitled) - Pathem, B. K.; Claridge, S. A.; Zheng, Y. B.; Weiss, P. S. (Annu. Rev. Phys. Chem., 2013)

(untitled) - Gust, D.; Moore, T. A.; Moore, A. L. (Chem. Commun., 2006)

(untitled) - Lennartson, A.; Roffey, A.; Moth-Poulsen, K. (Tetrahedron Lett., 2015)

(untitled) - Otsuki, J.; Tsujino, M.; Iizaki, T.; Araki, K.; Seno, M.; Takatera, K.; Watanabe, T. (J. Am. Chem. Soc., 1997)

(untitled) - Blanco, V.; Leigh, D. A.; Marcos, V. (Chem. Soc. Rev., 2015)

(untitled) - Senthilkumar, T.; Zhou, L.; Gu, Q.; Liu, L.; Lv, F.; Wang, S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Yu, J.-J.; Cao, Z.-Q.; Zhang, Q.; Yang, S.; Qu, D.-H.; Tian, H. (Chem. Commun., 2016)

(untitled) - Feringa, B. L. (Angew. Chem., Int. Ed., 2017)

(untitled) - Kassem, S.; van Leeuwen, T.; Lubbe, A. S.; Wilson, M. R.; Feringa, B. L.; Leigh, D. A. (Chem. Soc. Rev., 2017)

(untitled) - Sauvage, J.-P. (Angew. Chem., Int. Ed., 2017)

(untitled) - Stoddart, J. F. (Angew. Chem., Int. Ed., 2017)

(untitled) - Laptenok, S. P.; Gil, A. A.; Hall, C. R.; Lukacs, A.; Iuliano, J. N.; Jones, G. A.; Greetham, G. M.; Donaldson, P.; Miyawaki, A.; Tonge, P. J.; Meech, S. R. (Nat. Chem., 2018)

(untitled) - Zhang, X.; Zhang, M.; Li, D.; He, W.; Peng, J.; Betzig, E.; Xu, P. (Proc. Natl. Acad. Sci. U. S. A., 2016)

(untitled) - Hüll, K.; Morstein, J.; Trauner, D. (Chem. Rev., 2018)

(untitled) - Broichhagen, J.; Frank, J. A.; Trauner, D. (Acc. Chem. Res., 2015)

(untitled) - Lerch, M. M.; Hansen, M. J.; van Dam, G. M.; Szymanski, W.; Feringa, B. L. (Angew. Chem., Int. Ed., 2016)

(untitled) - Velema, W. A.; Szymanski, W.; Feringa, B. L. (J. Am. Chem. Soc., 2014)

(untitled) - Bléger, D.; Hecht, S. (Angew. Chem., Int. Ed., 2015)

(untitled) - Fihey, A.; Perrier, A.; Browne, W. R.; Jacquemin, D. (Chem. Soc. Rev., 2015)

(untitled) - Szymański, W.; Beierle, J. M.; Kistemaker, H. A. V.; Velema, W. A.; Feringa, B. L. (Chem. Rev., 2013)

(untitled) - Baroncini, M.; Groppi, J.; Corra, S.; Silvi, S.; Credi, A. (Adv. Opt. Mater., 2019)

(untitled) - Bandara, H. M. D.; Burdette, S. C. (Chem. Soc. Rev., 2012)

(untitled) - Irie, M.; Fukaminato, T.; Matsuda, K.; Kobatake, S. (Chem. Rev., 2014)

(untitled) - Klajn, R. (Chem. Soc. Rev., 2014)

(untitled) - Aprahamian, I. (Chem. Commun., 2017)

(untitled) - Yang, Y.; Hughes, R. P.; Aprahamian, I. (J. Am. Chem. Soc., 2012)

(untitled) - Shao, B.; Baroncini, M.; Qian, H.; Bussotti, L.; Di Donato, M.; Credi, A.; Aprahamian, I. (J. Am. Chem. Soc., 2018)

(untitled) - van Stokkum, I. H. M.; Larsen, D. S.; van Grondelle, R. (Biochim. Biophys. Acta, Bioenerg., 2004)

Methods in Enzymology - Henry, E. R.; Hofrichter, J. (Singular value decomposition: Application to analysis of experimental data, 1992)

(untitled) - Schultz, T.; Quenneville, J.; Levine, B.; Toniolo, A.; Martínez, T. J.; Lochbrunner, S.; Schmitt, M.; Shaffer, J. P.; Zgierski, M. Z.; Stolow, A. (J. Am. Chem. Soc., 2003)

(untitled) - Oulianov, D. A.; Tomov, I. V.; Dvornikov, A. S.; Rentzepis, P. M. (Opt. Commun., 2001)

(untitled) - Niesner, R.; Roth, W.; Gericke, K.-H. (ChemPhysChem, 2004)

(untitled) - Briš, A.; Trošelj, P.; Margetić, D.; Flamigni, L.; Ventura, B. (ChemPlusChem, 2016)

(untitled) - Snellenburg, J. J.; Laptenok, S. P.; Seger, R.; Mullen, K. M.; van Stokkum, I. H. M. (J. Stat. Software, 2012)